Sweet enough - Roman, Alison (Clarkson Potter/Publishers, 2023)
"A simple, stylish cookbook full of desserts that come together faster than you can eat them, from the New York Times bestselling author of Dining In and Nothing Fancy. Casual, effortless, chic: These are not words you'd use to describe most desserts. But before Alison Roman made recipes so perfect that they go by one name -- The Cookie, The Pasta, The Lemon Cake -- she was a restaurant pastry chef who spent most of her time learning to make things the hard way. She studied flavor, technique, precision...and distilled her knowledge to pare all that down into treats that get you the most deliciousness with the least amount of fuss. So the desserts you want to make right away -- whether you're craving cookies, cakes, or other sweet stuff -- you can make right away. Simple but sublime, Alison shows you how make sweets with her trademark casualness, like how to turn jam into a dessert (swirled into ice cream, folded into easy cake batter, spread onto a rough pastry dough). Make simple cakes that dirty only one bowl. Keep one crust recipe in your back pocket and turn it into any pie you want. Recipes like Salted Lemon Pie, Hot Buttered Rum Cake, and Toasted Rice Pudding make your sweetest dream come true in an instant. In Sweet Enough, Alison has written the book for people who think they don't have the time or skill to pull off dessert"--